A Treatise on The Science of Logic in Qassim Al-Khani Study and Investigation - EL BATAL, Soufiane (Nama Journal of Islamic Sciences and Humanities, 2023)
Our attempt to investigate and study the manuscript of A Treatise on The Science of Logic by Qassim Al-Khani aims to highlight the multiples problems that logic has triggered in the human thinking Throughout history, especially those related to the relationship between logic and philosophy. therefore we go into the completion of a general scene of different positions encountered by the logic industry in the Arab and Islamic civilization, as it became in one of its moments established on the philosophy of meaning after it was just logic that did not exceed the categories of Greece, until the problem ended on a stage related to the Arab expression, and the belief at this stage becomes that logic is Just a preparation for philosophy, not within it, and here the problematic of revelation and the language of the Qur’an became apparent in the picture. So, this was one of the reasons for the differentiation between "Greek logic" which is limited to analogy as the only way to knowledge, which ended with the establishment of a logic stemming from the Islamic belief that is suitable for use in divine demands, which is "the Qur'anic logic", and thus Aristotle's logic had been transcended, which was considered lost in a dead language because it does not explain the meanings, which is limited only in distinguishing truth from falsehood, instead of knowing the bottom of the subject (i.e. the language).